A comparative clinical study to evaluate the retention of the maxillary complete removable dentures bases using two different final impression materials (An In vivo study) - فضة أحمد; مجد سلمان (Latakia University Journal -Medical Sciences Series, 2023)
Objective: This study aimed to compare Polyether as a final impression (by a custom tray in the monophase technique) in terms of retention of the maxillary complete dentures bases with dentures bases which was made using low fusing impression compound and Zinc Oxide – Eugenol (ZOE). Also, to find out the possibility of being an alternative material for final impression. Materials & Methods: Ten patients had been grouped, and then two final impressions were made for the maxillary of each patient by a custom tray. The first final impression was made by low fusing impression compound followed by ZOE, and the second one was made by Polyether in medium viscosity in the monophase technique and without border molding. After that, a test for the retention of the maxillary complete dentures bases made from these materials was done for each impression. Results: The results showed there was no significant difference in the retention of the maxillary complete dentures bases made on the master casts made from both materials that been made by low fusing impression compound followed by ZOE, and Polyether in medium viscosity in the monophase technique and without border molding. Conclusion: The maxillary complete dentures bases made from the final impression of Polyether in medium viscosity in the monophase technique and without border molding have the same retention of the maxillary complete dentures bases made from the final impression by low fusing impression compound followed by ZOE.